1995
DOI: 10.1515/bchm3.1995.376.11.661
|View full text |Cite
|
Sign up to set email alerts
|

Activation Functions of Transcription Factor Sp1 at U2 snRNA and TATA Box Promoters

Abstract: To localize regions in the human transcription factor Sp1, which are involved in activating transcription of the U2 snRNA gene promoter and of a TATA box gene promoter, the activation potentials of GAL4/Sp1 chimeras were analyzed in mammalian cells. In vitro mutagenesis analysis of Sp1 showed that mutation of a hydrophobic amino acid residue in glutamine-rich activation domain A impairs stimulation of transcription from the TATA box promoter, but not from the U2 promoter. Furthermore, we found that similar par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Comparison of the four repeats revealed the presence of seven invariant residues located at positions 1,5,7,8,11,12, and 15 in each repeat (Fig. 7A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison of the four repeats revealed the presence of seven invariant residues located at positions 1,5,7,8,11,12, and 15 in each repeat (Fig. 7A).…”
Section: Resultsmentioning
confidence: 99%
“…Based on our work, we propose that the two separate Staf activation domains are involved in two different transactivation mechanisms: one for the specific activation of mRNA promoters and the other for that of snRNA and snRNA-type promoters. Forsberg et al (11) showed that Sp1 is able to stimulate transcription from mRNA and snRNA promoters. However, it must be pointed out that in this case overlapping domains are involved, while we identified two distinct, specialized domains in Staf.…”
Section: Discussionmentioning
confidence: 99%
“…The Gal4-Sp1 fusion protein contained the first 612 amino acids of the Sp1 protein and a Gal4-DBD at the C-terminus [48]. The Sp1-specific sequence within this fusion protein includes the major activation domains A, B and most of C, but lacks the activation domain D and the DBD [49].…”
Section: Pma Does Not Increase Expression or Transcriptional Activitymentioning
confidence: 99%
“…(B) Effect of Gal4-Sp1 or Gal4-DBD on the wild-type or Gal4-P3 promoter in the presence or absence of PMA. The Gal4-Sp1 fusion protein contains the first 612 amino acids of the Sp1 protein, whereas the Sp1-DBD at the C-terminus was replaced by the Gal4-DBD [48]. The Gal4-PTHrP P3 promoter contains a Gal4-binding site between − 63 and − 47, which replaces the Sp1-binding site (Figure 2A) [21].…”
Section: Pma Abrogates Binding Of An Mcf-7 Nuclear Protein To a Sequementioning
confidence: 99%
“…The plasmid -120/TATA(GAA) was constructed by changing the sequence (-30)TAGAAA(-25) to (-30)GAAAAA(-25), and the plasmid-120/TATA(G3T) was constructed by substituting the sequence ( -30)TAG-AAA(-25) for (-30)TATAAA(-25). To construct a reporter gene with GAL4 binding sites immediately upstream of the minimal LRP-2 promoter (-35 to +52), an oligonucleotide with Kpnl overhangs containing two tandem copies of the UAS (Forsberg et al, 1995) was ligated to Ä^nl-digested -35/wt. All constructs were verified by sequencing.…”
Section: Plasmid Constructsmentioning
confidence: 99%